Ganesa And His Cult In Contemporary Thailand - Agarwal, Ruchi; Jones, William J. (Penerbit Universiti Sains Malaysia (USM Press), 2018)
Ganesa has long been familiar to the people of Thailand but increasingly evident are the Ganesa cults ﬂourishing in Bangkok. In the process, the deity appears to be acquiring new roles and functions. Ganesa now serves in a number of capacities for some; he is a “fxer,” a deity of last resort that can help devotees to overcome obstacles in their lives. Not surprisingly, the growing popularity of the deity is reﬂected in a rapidly expanding trade in Ganesa images and icons, displayed in shopping mall exhibitions in a variety of forms, colours, shapes and sizes. Readily available at most of Bangkok’s major retail outlets, Ganesa icons are traded online via social media. This paper attempts to explore this phenomenon, both by examining shifting belief practices associated with Ganesa locally and by looking at how these shifts are reﬂected in the evolving trade in Ganesa iconography. Considering both together, the authors will demonstrate that Ganesa cult is presently the focal point for a number of people, each with its own unique approach to the deity, powers and representation.